Penerapan Standard Operating Procedure (SOP) Pengolahan Makanan Menu Ala-Carte Section Asia di Restaurant 209 Hotel Vasa Surabaya - Alkisah Nazilatul Riskiyah Finda Putri; Niken Purwidiani; Ila Huda Puspita Dewi; Mauren Gita Miranti (Pusat Riset dan Inovasi Nasional, 2024)
Implementation Standard Operating Procedure (SOP) in processing is very important to ensure consistency of taste, aroma, texture, and appearance. Restaurant 209 at Hotel Vasa faced the challenge of maintaining the consistency of its dishes, especially the Oxtail Soup which is highly demanded by guests. Inconsistency in dishes occurs due to variations in interpretation and execution of procedures by staff. So it is very important to apply SOPs in food processing. Focus of this research aims to determine the application of the SOP for food processing in the of Ala-carte Section Asia menu in Restaurant 209 Hotel Vasa Surabaya. In this study using a qualitative method, by collecting data through interviews, literature studies, and documentation. From the results of research obtained through interviews with kitchen staff, it can be concluded that the application of food processing SOP at Restaurant 209 Hotel Vasa Surabaya requires various stages in handling it, starting from maintaining personal hygiene, maintaining neatness and cleanliness of the work environment, preparing necessary ingredients, checking the quality of ingredients, processing food in accordance with standard recipes, being able to, operate tools in the kitchen, and monitor (control food) the cooking process. There are some SOP that have not been fully implemented by staff,such as not following the proper SOP in thawing the ingredients to be used. To overcome this problem, Hotel Vasa Surabaya provides briefings by the executive chef on the importance of carrying out work in accordance with the applicable SOP through regular control and evaluation, as a reminder for the staff to be consistent in their work.